Hindi Picture Word Articulation Test Development and Standardization - Kacker. S.K., Vijayalakshmi Basavaraj, Anuj Thapar Niranjini, Menon Rajiv Vasudeva (Journal of All India Institute of Speech and Hearing, 1970)
The present study aimed at constructing a picture articulation screening test in Hindi, for the hearing impaired children who have limited vocabulary. 48 Hindi Speech Sounds were tested using sixty eight familiar picturable words. Most of the sounds were tested in all the three positions in a words. The test was administered to 180 children in the age range of 3 to 6 years, to obtain norms for the acquisition of Hindi Speech Sounds. They were selected fromthe Vernacular schools in New Delhi. On the basis of the criteria for acquisition of sounds as the 50th percentile point, all the Hindi Speech Sounds were found to be acquired by the Children in the age range of 3 to 31/2 years itself. The test has its applicability in studying the articulatory status of the hearingimpaired.